Comparison of Pre-Oxygenation Using High-Flow Nasal Oxygen vs Tight Face Mask During Rapid Sequence Induction - Raza, Ali; Qureshi, Salman Athar (Biological and Clinical Sciences Research Journal, 2025)
Pre-oxygenation prior to rapid sequence induction (RSI) is critical in minimizing the risk of hypoxemia during emergency surgeries. High-flow nasal oxygen (HFNO) has emerged as a promising alternative to conventional facemask pre-oxygenation; however, data from multicenter, real-time emergency settings remain limited. Objective: To compare the effectiveness of high-flow nasal oxygen versus tight-fitting facemask pre-oxygenation in preventing desaturation during RSI among adults undergoing emergency surgery. Methods: This randomized controlled trial was conducted at the Anesthesia Department of Gujranwala Teaching Hospital between September 2024 and February 2025. A total of 144 adult patients requiring emergency surgery and RSI were randomized equally into the HFNO group (n=77) and facemask group (n=77). All participants were pre-oxygenated with 100% oxygen. The primary outcome was the incidence of oxygen desaturation (SpO₂ <93%) from the start of pre-oxygenation to one minute after tracheal intubation. Secondary outcomes included rates of regurgitation and end-tidal carbon dioxide (EtCO₂) levels post-intubation. Statistical analysis was performed using the Chi-square test, and p ≤ 0.05 was considered significant. Results: Desaturation <93% occurred in 5 patients (2.9%) in the HFNO group and six patients (3.4%) in the facemask group (p = 0.77), indicating no significant difference. No increase in desaturation risk was noted during on-call hours. Regurgitation rates and EtCO₂ levels after intubation were comparable between groups. No adverse events related to either technique were reported. Conclusion: Both high-flow nasal oxygen and tight-fitting facemask pre-oxygenation are safe and effective in maintaining adequate oxygenation during RSI in emergency surgeries. HFNO offers comparable outcomes and may be considered a viable alternative, particularly in settings where facemask pre-oxygenation may be less practical.